(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the prevalence of adherence to antiretroviral therapy among pregnant women using three assessment methods, compare adherence across these methods, and identify risk factors for non-adherence. Method: A cross-sectional study was conducted with pregnant women receiving care at a high-risk prenatal clinic of a tertiary hospital in southern Brazil. Participants completed an interview that included sociodemographic and clinical data collection, as well as the administration of an instrument for assessing adherence to antiretroviral therapy. Laboratory HIV viral load data and pharmacy dispensing records were also used to measure adherence. The study was approved by the Research Ethics Committee. Results: Forty-one pregnant women participated. Adherence rates varied depending on the assessment method: viral load suppression (78.0%), frequency of medication withdrawal from the pharmacy (31.7%), and the validated adherence scale (29.3%). The three methods showed no agreement. Older pregnant women, those with more children, higher levels of education, and more prenatal visits were more likely to adhere to treatment. Conclusion: Adherence to antiretroviral therapy among pregnant women living with HIV was insufficient, increasing the risk of vertical transmission. The different assessment methods yielded divergent results. Factors such as age, number of children, education level, and prenatal attendance influenced adherence. The findings highlight the importance of combining different assessment methods to obtain a more comprehensive understanding of patients’ treatment-related needs.